Electronic Music Review Nº 4 - von Reichenbach, Fernando (1968)
Revista-Contenido: Introduction to Tape Rocording ( Robert A. Moog) The Quality Race ( Walter Carlos, Benjamin Folkman) A Report on Tape Recorders ( Gordon Mumma) Multi-Track Recording in Electronic Music ( Walter Carlos, Benjamin Folkman) The MRS Recorder (Gerald S. Macdonal ) Noise Reduction in Electronic Music ( Ray M. Dolby) The Newell Tape Transport ( Eugene M. Zumchak) Electronic Music and Music Education ( Wayne Barlow) Review (Hugh Davies )